THE RESULTS OF OBSERVATIONS OF MUTUAL PHENOMENA OF THE GALILEAN SATELLITES OF JUPITER IN 2009 AND 2015 IN NIKOLAEV ASTRONOMICAL OBSERVATORY - Pomazan, A.; Maigurova, N.; Kryuchkovskiy, V. (Одеські астрономічні публікації, 2016)
The Earth and Jupiter once in 6 years have simultaneous passage of the ecliptic plane due to their orbital movement around the Sun. This makes it possible to observe the mutual occultations and eclipses in the Galilean satellites of Jupiter. We took part in the observational campaigns of the mutual phenomena in 2009 and 2014-15. The observations were made with a B/W CCD camera WAT-902H at the telescope MCT (D = 0.115 m, F = 2.0 m) of the Nikolaev Astronomical Observatory. The light curves of mutual phenomena in the satellites of Jupiter were obtained as a result of processing photometric observations. The exact moments of maximum phases and the amplitudes of the light variation have been determined from the analysis of the light curves. The data sets for the light curves have been sent in the IMCCE (Institute de Mecanique et de calcul des ephemerides, France) that coordinates the PHEMU campaigns.